P194 Endoscopy safety incidents reported in a national data set – a human factors analysis. (19th June 2022) - Ravindran, Srivathsan; Matharoo, Manmeet; Healey, Chris; Coleman, Mark; Ashrafian, Hutan; Darzi, Ara; Thomas-Gibson, Siwan
Abstract : Introduction: Outside of procedural adverse events, there is little understanding of wider patient safety incidents (PSIs) in endoscopy. The aim of this study was to quantify endoscopy PSIs and identify their contributory human factors utilising a national data set. Methods: Data were extracted from the National Reporting and Learning System (NRLS) which records staff-reported safety incidents in England and Wales. Two independent coders with backgrounds in safety and qualitative analysis coded data using a hybrid thematic analysis approach. The Human Factors Analysis and Classification System (HFACS) was applied to code contributory factors. Results: From 2017-2019, 1811 endoscopy-related PSIs were identified, of which 629 were procedural adverse events (pAEs; directly related to procedure), 539 were non-procedural adverse events (nAEs; any incident not directly related to a procedure) and 16 were 'never' events. Inter-coder reliability was substantial (kappa 0.77). 842 human factors codes were identified across four levels: acts, preconditions, supervision and organisational influences. Decision-based errors were the most common acts (>40%) across categories ( table 1 ). Patient factors were significant contributors in pAEs (74.5%) and co-ordination, communication (33.5 – 66.7%) and situational (27.1%) factors were key contributors in nAEs and never events. Conclusions: This is the first overview of national-level endoscopy safety incident data and demonstrates the role human factors play in PSI development. These findings should inform patient safety improvement strategies in endoscopy.